Specialized meat semi-finished products for prevention of liver diseases - O. P. Boleshenko; M. A. Aslanova; A. L. Bero (Пищевые системы, 2021)
Dietetic therapy plays an important role in prevention and treatment of non-communicable, alimentary-dependent diseases including the bile duct diseases and chronic liver injury. The medico-biological requirements for the composition and quality of specialized semi-finished products for prevention and treatment of liver diseases are formulated and formalized in the paper. Using the methods of the computer design, the recipe of the specialized minced meat semi-finished product from horse meat, which is nutrient adequate to specific features of nutrition of patients with liver diseases, was developed and optimized. The experimental recipe of minced semi-finished products consists of horse meat of the second grade, soy protein fiber, soy protein isolate, textured soy flour, milk thistle oil meal, chicken eggs, soybean oil, salt, onion, vitamins B1, B2 and E, magnesium and zinc salts. The biological value of the obtained product is characterized by the high indices of the amino acid balance (Cmin=0.99, σс =0.85, U=6.27) and fatty acid balance of lipids ((RLi) I = 1…3 = 0.9 and (RLi) I = 1…6 -0.77). The content of dietary fibers, vitamins B1 and B2 as well as mineral salts of magnesium and zinc in the semi-finished product corresponds to the medico-biological requirements. The effectiveness of the developed product was confirmed in the experiment of the laboratory mice with simulated liver cirrhosis. The results of the assessment on the laboratory animals show that the developed product positively influences the processes of metabolism in the mouse body. The coefficient of protein assimilation in the group of animals fed with the specialized product was 25% higher than in animals received the standard vivarium diet. The biochemical blood analysis showed that intake of the developed product reduced the content of bilirubin, cholesterol, AST and ALT in the animal body by 34.5%, 8.2%, 11.0% and 12.5%, respectively.